Urgensi Taman Bacaan Masyarakat dalam meningkatkan literasi,Pendidikan dan Minat Baca Anak-Anak di Desa Sambungo Kecamatan Silaut Kabupaten Pesisir Selatan - Annisa Fitri; Solfema Solfema; Lili Desa Putri (BADAN PENERBIT STIEPARI PRESS, 2025)
Community Reading Park (TBM) for children's education and interest in reading inSambungo Village, Silaut District, Pesisir Selatan Regency, West Sumatra. This discussion focuses on examining the extent of TBM's role in improving the quality of education and fostering a culture of literacy among children in rural areas. Learning at TBM has a positive impact on children's educational development, which is characterized by increased interest in reading, literacy skills and academic achievement. Excellent programs such as interactive fairy tales, reading clubs, and tutoring are effective in creating a pleasant learning atmosphere. The influence of learning activities at the Community Reading Garden (TBM) on children's education and interest in reading in Sambungo Village, Silaut District, Pesisir Selatan Regency , (1) increasing children's academic achievement at school, especially in reading ability and reading comprehension; (2) development of independent reading habits among children; (3) increasing children's literacy skills and general knowledge through various interactive learning activities at TBM; and (4) more time spent reading.